Linguistic Aspects of Sound Design for Theatre: A View from the Fringe - Cousins, Rick (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2016)
Although sound design is a well-established part of the toolkit for creating theatre, its function in creating meaning for performance texts is often overlooked in discussions of the relative semiotic importance of various scenic arts. Many of the most cogent observations and theories concerning the use of sound as a parallel to spoken language in performed narrative come from scholars and practitioners whose specialty is not theatre, but radio drama. Using these theories, and the deeper analyses of linguistic structure proposed by Roman Jakobson as benchmarks, this is a preliminary survey of the resemblances between sound design and conventional forms of linguistic communication. The territory mapped is the world of small-venue touring fringe theatre, with a special focus on the roles that time and timing play in determining the semiotic content of designed sound in a performative setting.